‘Do Not Separate Sexuality Education from Religious Teachings’: Parents’ Perceptions and Suggestions towards Sexuality Education in Uganda - Bweyale, Josephine; Sekaye, Nanfuka Annette (East African Journal of Traditions, Culture and Religion, 2023)
The Uganda government designed a framework to teach sex education in Uganda primary schools starting from pre-primary school at the age of three up to high school. Sexuality Education (SE) is intended to be a school intervention to provide the right information to young people misled by peers, the media, and social networks that are now easily accessible. Besides, sexuality education is meant to be a school-based intervention to curb the increasing rates of premarital pregnancies that lead to school dropouts of teenage girls. However, the mention of sexuality education creates unease among parents, teachers, and policymakers. There are arguments and counterarguments that sex education potentially leads children into sexual immorality and permissiveness and sexualises the children. On the other hand, there are sections of people who are convinced that sex education is important and timely and important in Uganda. There have been barriers to the implementation of sexuality education in different contexts. The barriers include political, cultural, religious, and social concerns that influence the effective implementation of sexuality education. Besides, parents are critical in implementing any teaching about sexuality because they provide basic sexual information and knowledge to their children. For instance, they discuss issues concerning hygiene, and sexual health, such as STDs, abstinence, virginity, and relationships with their children. Binti et al. (2020) and Turnbull et al. (2008) stated that parents are influential in teaching sex education because they influence their children’s behaviours and sexual identity formation. Therefore, their opinions and attitudes are fundamental in handling sex education. In African contexts, parents impart knowledge and skills about puberty, courtship, and marriage. It is against this basis that the article discusses the perceptions and attitudes of parents towards teaching sex education in primary schools in Uganda. The article focuses on the following questions; (i) Is there a need for sexuality education? (ii) What is the appropriate content for sexuality education? (iii) Who is the best teacher for sexuality education? and (iv) What is the appropriate age for sexuality education in Uganda?